126k views
1 vote
Find (w² + 1)(w³ - w + 1).

1 Answer

0 votes

Answer:

Product is
w^5+w^2-w+1

Explanation:

Given:
(w^2+1)(w^3-w+1)

Simplify the product of polynomial.

It is product of binomial with trinomial.


\Rightarrow (w^2+1)(w^3-w+1)


\Rightarrow w^2(w^3-w+1)+1(w^3-w+1) (Distributive property)


\Rightarrow w^2\cdot w^3-w^2\cdot w+w^2\cdot 1+w^3-w+1 (Distributive property)


\Rightarrow w^5-w^3+w^2+w^3-w+1 (combine like term)


\Rightarrow w^5+w^2-w+1

Product is
w^5+w^2-w+1

User SplinterReality
by
6.0k points